PENGARUH PENEMPATAN KERJA, KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP MOTIVASI SERTA DAMPAKNYA PADA KINERJA PEGAWAI DI FAKULTAS TEKNIK UNIVERSITAS UDAYANA - Ayu Harum Prima Sari; I Putu Santika (Journal of Applied Management Studies, 2020)
The purpose of this study is to determine whether work placement, work characteristics and work environment have a significant direct effect on employee motivation and performance, whether motivation has a significant effect on employee performance and to find out whether work placement, work characteristics and work environment have a significant indirect effect on employee performance at the Faculty of Engineering, Udayana University. The respondents of this study were 51 employees. Methods of data collection using questionnaires, interviews and archives, this study uses Path Analysis techniques.Keywords: job placement, job characteristics, work environment, motivation and employee performance.